Chronobiological types, duration of sleeping and psycho-emotional condition of teenagers - Petronytė, Lina; Praninskienė, Rūta (Acta medica Lituanica, 2017)
Sleep is a biological process that operates according to day and night cycles. This self-regulatory system is universal in all organisms, including humans and mammals. For this reason, the  topic is widely analysed in the existing literature; however, no studies about chronobiological types of teenagers have been conducted in Lithuania before. 253 schoolchildren, 13 to 18 years of age, were surveyed in schools of Vilnius and Panevėžys, Lithuania. Responses were gathered during the period from September 2013 to February 2014. The survey consists of four parts: demographical data, Morningness-Eveningness Questionnaire, PedsQL 4.0 survey of life quality, and HADS – Hospital Anxiety and Depression Survey. In total, 115 (45.5%) boys and 138 (54.5%) girls participated in the survey. On average, boys sleep 7.10 (±1.27) hours, compared to 6.79 (±1.20) (p = 0.05) hours for girls. 94 (37.2%) survey participants feel sleepy and/ or very sleepy at school. 133 (52.6%) respondents find it difficult/very difficult to wake up in the morning. 218 (86.2%) respondents use the computer before going to sleep: 96 (83.5%) boys and 122 (88.4%) girls. Based on a  subjective evaluation, 187 (73.9%) respondents categorize themselves as the evening type and 66 (26.1%) as the morning type. 13 (5.1%) respondents exhibit symptoms of depression. The majority of the  respondents categorize themselves as evening/ middle chronotypes. The average duration of sleep is 6.93 (±1.24) hours. 86.2% of the respondents use the computer before going to sleep. Half of the children may have difficulties waking up in the morning. One out of three children feels sleepy at school.
Keywords: teenagers; chronobiological types; life quality